The Role of Governance in Mobile Phones for Inclusive Human Development in Sub-Saharan Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
This study assesses the synergy effects of governance in mobile phone penetration for inclusive human development in Sub-Saharan Africa with data for the period 2000-2012 by employing a battery of interactive estimation techniques, namely: Fixed effects (FE), Generalised Method of Moments (GMM) and Tobit regressions. Concepts of political (voice & accountability and political stability/no violence), economic (government effectiveness and regulation quality) and institutional (corruption-control and rule of law) governance are employed. The following findings are established. First, the previously apparent positive correlation between mobile phones and inclusive development can be extended to a positive effect. Second, whereas political governance is overwhelmingly not significant across estimated models, average effects from economic governance are higher relative to institutional governance. Third, on the synergy effects from interactions between mobile phones and governance variables, whereas none are apparent in FE regressions, there are significant synergy effects in GMM and Tobit estimations, notably, from: (i) regulation quality in the former and (ii) political stability, voice & accountability and rule of law in the latter. Fourth, there is consistent evidence of convergence in inclusive human development. Policy implications are discussed.
Keywords: G20; I10; I32; O40; P37; 330; Mobile phones; governance; inclusive human development